2016
DOI: 10.1111/ajt.13908
|View full text |Cite
|
Sign up to set email alerts
|

Estimated or Measured GFR in Living Kidney Donors Work-up?

Abstract: The value of estimated glomerular filtration rate (eGFR) in living kidney donors screening is unclear. A recently published web-based application derived from large cohorts, but not living donors, calculates the probability of a measured GFR (mGFR) lower than a determined threshold. Our objectives were to validate the clinical utility of this tool in a cohort of living donors and to test two other strategies based on chronic kidney disease epidemiology collaboration (CKD-EPI) and on MDRD-eGFR. GFR was measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 17 publications
3
21
0
1
Order By: Relevance
“…This observation is in accordance with what was reported regarding the relationship between eGFR and mGFR among potential donors [19]. Moreover, we recently published two studies showing that mGFR (and not eGFR) divided by the volume of the remaining kidney could be used to predict functional gain of the remaining kidney following donation [20] and that measured GFR could not be predicted precisely by calculators or equations for nearly 60% of donors [19]. For these reasons, we think that eGFR cannot replace mGFR in living donor screening.…”
Section: Discussionsupporting
confidence: 94%
“…This observation is in accordance with what was reported regarding the relationship between eGFR and mGFR among potential donors [19]. Moreover, we recently published two studies showing that mGFR (and not eGFR) divided by the volume of the remaining kidney could be used to predict functional gain of the remaining kidney following donation [20] and that measured GFR could not be predicted precisely by calculators or equations for nearly 60% of donors [19]. For these reasons, we think that eGFR cannot replace mGFR in living donor screening.…”
Section: Discussionsupporting
confidence: 94%
“…One study validating these computations in donor candidates has been reported. 131 Future studies should address prediction accuracy among racial and ethnic groups for whom the accuracy of eGFR is less certain (eg, nonblack, nonwhite persons).…”
Section: Measurement Methodsmentioning
confidence: 99%
“…The second eGFR could either be derived from Scr and cystatin C levels or simply be a repeat assessment of eGFR using Scr level alone. [26][27][28][29] This recommendation is a substantial departure from current practice in the United States 27 and would not be compliant with current UNOS policy. For transplantation programs to use this approach yet be compliant with UNOS policy, that policy would first need to be revised.…”
Section: Commentarymentioning
confidence: 99%